A postura dialógica do Sócrates platônico no Górgias e no Hípias Maios e as perspectivas para uma educação problematizadora / João Gilberto Hubert Novakoski - Novakoski, João Gilberto Hubert (2012)
The present paper is based on Socrates platonic dialogue analysis to be able to theme and manifest perspectives towards a problematized education. Socrates has not been a professor or educator in the literal meaning of the words, he himself used to say that did not hold a great knowledge about anything. This behavior of attesting he did not know or to declare ignorance about things guided him to analyse himself constantly and to instigate this attitude in others, mainly among the interlocutors of the debates that he used to established. Socrates, in order to be able to deal with this practice, developed a kind of pedagogical methodology, by using the resources such us irony, the elenchus and Aporia, which enriched the meaning of the dialogues. These mechanisms so necessary to the dialogue development, had the pedagogical effect of desinstalling the interlocutors the knowledge idea they used to defend. Therefore, the Socrates character does not function in professor basis, but as an instigating pedagogy to lead the interlocutors to know more and analyse their own existence. We defend the Socratic posture present in the first phase of Platon, particularly in Górgias and Greater Hípias, it has an educational characteristic because it objectives not only desinstalling the interlocutor knowledge but also and mainly to provoke the self-analysis and as a consequence the selfbuilding up through the means of the Elenchus, the irony and Aporia mechanisms. Our work proposes to identify some fundamental characteristics from the exposition of the methodological questions related to platonic Socrates and the delimitation of both dialogues of Platon first phase Górgias and Greater Hipias, expose Socrates dialogue postures and extract educational consequences of its posture, indicating the possibilities to the Socratic pedagogy towards a more Problematized Education